Anti-cancer Drugs Nature, Synthesis and Cell - Bankovic, Jasna (IntechOpen, 2016)
We are in constant search for new therapeutic options to cure cancer. In this book, you can find out how scientists throughout the world deal with this problem. Readers will learn how to engage nature, chemical synthesis, and cell machinery to design new anticancer agents. Nature has already been very generous in providing us different compounds which are in widespread application. Starting from these resources, various synthetic processes are applied to create synthetic drugs which can be then obtained in large quantities. Also, the cell by itself provides different possibilities to meet the constantly increasing requirements for successful therapy. Explore the book and find out what are the new ways to fight cancer.